Pembangunan Aplikasi Sistem Informasi Pergudangan pada Rumah Sakit Umum Daerah Dr. Murjani Sampit Kabupaten Kotawaringin Timur - Hidayatullah Agung Prasetyo; Bayu Priyambadha; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The information technology development is growing rapidly and the main problem is how to process data to give useful information and easy to use by user. Warehouse management system that curently used on Dr. Murjani Sampit hospital is manual. Data recording done by write on books and excel files, with the number of in and out of goods makes record and search for data become inefficient in term of time and effort. Assigning tasks to someone who did this manual system led to possible errors in writing and data processing. From these problems it is necessary to develop an information system application that can handle recording, storing, processing and reporting automatically to make work easier and reduce data processing error. Research was done by Iterative Life Cycle and system builted using PHP, MySQL, and Javascript technology. Compatibility testing showed system running well on Google Chrome and Firefox Mozzila later on white-box testing showed from 20 test cases 100% result is valid and from black-box testing obtained from 65 test cases 100% result is valid. The results of these tests indicate that the system successfully analyzed its needs and implemented according with the design.System implementation may resolve the manual system problem which occur at the hospital.